(untitled) (Mustansiria Dental Journal, 2019)
Aim: This clinical study is to investigate the effect of fasting (Sawm) Ramadan on the count of streptococcus mutans in plaque surrounding fixed orthodontic appliances. Materials and Methods: Fifteen patients with orthodontic appliances were participated in this study. Plaque specimens were collected from those patients at two occasions, during Rmadan fasting (Sawm) and after they break there fasting after Ramadan. The plaque Streptococcus mutans number of colony-forming units (CFU) was analyzed by using Dentocult SM Strip mutans test. Results: This study demonstrated highly significant difference in Streptococcus mutans (CFU) counts in plaque between the values obtained from fasting patients during Ramadan and when they are breaking the fast after Ramadan. Conclusions: during Ramadan fasting, persons change timing and types of their food and beverages consuming as well as teeth cleaning habits. Therefore orthodontist should be aware of their patients’ oral hygiene during Ramadan by promoting and maintaining satisfactory teeth cleaning during fasting (Sawm) and Iftar hours.